Relationship between Employees’ Recognition of Contribution and Job Satisfaction (A Study of Secondary School Teachers in Kogi State, Nigeria) - Olajide, Orebiyi, Anthony; Kola, Adesina, Ibrahim; Adeyemi, Obalanlege (Global Journal of Social Sciences Studies, 2019)
This study examined relationship between employees’ recognition of contribution and job satisfaction. The study adopted a survey research method using Structured questionnaire, Focus Group Discussion and In-depth Interviews. Four Hundred Secondary School Teachers in the services of Kogi State Teaching Service Commission were randomly selected from 10 schools in each of the three senatorial districts of the state. Data were analysed using frequency counts, percentages, mean and simple regression. Results show all items measuring employers’ recognition of contribution met the criterion for acceptance: acknowledgement of good work attracts a mean score of 4.48; Equal opportunities for in-service (3.44); Assurance of promotion for good performance (3.67); Promotion based on merit (3.08); Equal opportunity to become principal (3.29), and method of salary payment (2.86). As for the teachers’ perception of job satisfaction, all items designed to measure this variable, except one, met the criteria for acceptance (2.5); opportunity for professional growth is restricted, had a mean score of 2.0 which is below the cut of point of 2.5. The regression analysis shows a significant relationship between employers’ recognition of contribution and job satisfaction (P < 0.01). The study recommends that management must put in place a structure that will guarantee appreciation of good performance.